Evidence that changes the way you practice - Bipolar disorder: Mania and depression explained - K. Outhoff (South African Family Practice)
Bipolar disorder is characterised by alternating discrete episodes of depression and mania. Rational pharmacotherapy necessitates an appreciation of these different phases and of the possible underlying pathophysiology. A greater understanding of the pathogenesis of bipolar disorder has boosted awareness of how anti-bipolar drugs work, and vice versa. This bidirectional relationship has amplified knowledge in both disciplines.